Do Computational Thinking and Self Regulated Learning Affect Computer Programming Problem Solving Skills? : An Experimental Study - Susilowati, Dyah; Rahim, Abdul; Ananta, Gede Pramudya; Saputri, Dian Syafitri Chani; Hasanah, Uswatun; Ria, Reny Refitaningsih Peby (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the effect of computational thinking and self regulated learning on computer programming problem-solving skills. The research used a quasi-experiment with a factorial design. Research sampling using a purposive sampling technique. The sampling of this study used a purposive sampling technique, namely students of Bumigora University, Indonesia. The data collected were in the form of tests with data analysis techniques using inferential statistics. The results showed the fulfillment of the prerequisite tests of normality and homogeneity with each Sig value obtained > 0,05. The paired sample t-test test in the control and experimental groups obtained each Sig value < 0.05, so it can be concluded that there is a significant difference in student learning outcomes in each control group and experimental group. The independent sample t-test test obtained a Sig value < 0.05, so it can be concluded that there is a significant difference between the computational thinking method and the conventional learning method. The independent sample t-test test obtained a Sig value < 0.05, so it can be concluded that there is a significant difference between high and low self-regulated learning. Factorial ANOVA test obtained Sig value <0.05, so it can be concluded that the interaction between learning methods and self-regulated learning makes a significant difference in the ability to solve computer programming problems. The implications of applying computational thinking methods and developing self-regulated learning skills significantly improved problem-solving skills in computer programming, thus supporting the need to integrate this approach into curricula and teaching strategies.